Structure and function relationship of formate dehydrogenases: an overview of recent progress - Kobayashi, Ami; Taketa, Midori; Sowa, Keisei; Kano, Kenji; Higuchi, Yoshiki; Ogata, Hideaki (IUCrJ, 2023)
Formate dehydrogenases (FDHs) catalyze the two-electron oxidation of formate to carbon dioxide. FDHs can be divided into several groups depending on their subunit composition and active-site metal ions. Metal-dependent (Mo- or W-containing) FDHs from prokaryotic organisms belong to the superfamily of molybdenum enzymes and are members of the dimethylsulfoxide reductase family. In this short review, recent progress in the structural analysis of FDHs together with their potential biotechnological applications are summarized.